(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To compare cell-mediated and humoral immunity characteristics of patients with T1 to T3 CM treated with photocoagulation (PC) combined with strontium-90 (Sr90)/ yttrium-90 (Yt90) brachytherapy (BT)) versus transpupillary thermotherapy (TTT) combined with Sr90/Yt90 BT. Material and Methods: Eighty-seven patients with T1 to T3 CM were included in the study. Group 1 (TTT plus BT) included 31 patients, group 2 (PC plus BT) included 56 patients, and the control group included 44 healthy individuals. Groups were comparable in terms of age, gender and tumor location. Results: The following parameters were significantly increased (р < 0.009) in group 1 compared to controls and group 2: leukocytes (by 1.1 thousand cell/µl and 1.3 thousand cell/µl, respectively), absolute counts and percentages of lymphocytes (by 0.6 thousand cell/µl and 1.0 thousand cell/µl, and by 5.5% and 10.3%, respectively), absolute counts of CD3+ T cells (by 376.2 thousand cell/µl and 520.0 thousand cell/µl, respectively), CD4+ T helpers (by 351.2 thousand cell/µl and 362.0 thousand cell/µl, respectively), CD8+ T suppressors (by 125.8 thousand cell/µl and 133.8 thousand cell/µl, respectively). In addition, there was an increase in absolute counts and percentage of phagocytic neutrophils (by 953.0 thousand cell/µl and 18.5%, respectively) compared to controls, absolute counts of СD16+ NK cells compared to controls and group 2 (by 88.5 thousand cell/µl and 119.2 thousand cell/µl, respectively), absolute counts of СD19+ B cells compared to group 2 (by 166.7 thousand cell/µl) and absolute counts of IgA compared to controls (by 0.5 g/l) and IgM compared to controls and group 2 (by 0.4 g/l and 0.7 g/l, respectively). Moreover, the CD4+/CD8+ ratio was by 2.2 increased compared to controls and by 1.0 decreased compared to group 2. In group 1, there was a decrease in the percentages of CD3+ (by 13.3%) and CD4+ (by 14.5%) compared to group 2, and absolute counts of IgG (by 2.0 g/l) compared to controls. The only substantial changes in immunological parameters with treatment were an increase in the percentage of NK cells by 4.3% (р = 0.02) in group 1 and a reduction in the percentage of phagocytic neutrophils by 15.8% (р = 0.0000) and an increase in IgM by 0.2 g/l (р = 0.002) in group 2. Conclusion: We found that, at baseline, patients with T1 to T3 CM had an active immune response to tumor antigens. In addition, they exhibited no statistically significant changes in the parameters of cell-mediated and humoral immunity after treatment with TTT (delivered using the developed methodology) combined with Sr90/Yt90 BT, excepting an increase in the percentage of NK cells by 4.3% (р = 0.02).